Individual Characteristics and Punitive Practice for the Women Accused of Illegal Possesion and Distribution of Drugs or Psychoactive Substances - Jarutienė, Liubovė (Kriminologijos studijos, 2022)
According to the official statistical data, in Lithuania, female offenders make up approximately 10% of the convict population and 5% of the prison population (Department of Statistics, 2022). Due to rather small numbers of women drawn into the criminal world, female offenders and their specific needs are often hardly visible to the representatives of the law enforcement and correctional system. Therefore, the punitive practices applied to female offenders as well as the social context of their criminal behavior remain understudied topics in Lithuania. The main purpose of this study is to uncover the individual characteristics and the offending circumstances of the women accused of illegal posession and distribution of drugs. Also, this study includes the analysis of the sentencing trends for female culprits of drug-related crimes. The analysis of court practice and the interviews with the sentenced women has shown that, compared to males, females had no stable source of income and had to take care of the children and other family members more often. In addition, unlike males, females did not distribute drugs in the organized criminal groups, while the additional offences were mostly related to drug abuse rather than any other complicated criminal scheme. Finally, the comparison of sentencing trends has shown that Lithuanian courts tend to be more merciful towards women as they where imposed with shorter prison sentences. This study is one of the few attempts to explore the social context of female criminal behavior which will hopefully encourage to individualize the sentences imposed to female offenders.